LOST AND FOUNDER : A PAINFULLY HONEST FIELD GUIDE TO THE STARTUP WORLD - Fishkin, Rand (New York, New York : Portfolio/Penguin, 2018)
Rand Fishkin, the founder and former CEO of Moz, reveals how traditional Silicon Valley "wisdom" leads far too many startups astray, with the transparency and humor that his hundreds of thousands of blog readers have come to love.
Includes index
Keywords: Internet -- Industry -- United States; New businesses -- United States; Entrepreneurship -- United States